Nonprofit investment & development : a guide to strategies and solutions for thriving in today's economy - Matloff, Roger, 1959-; Chaillou, Joy Hunter, 1969- (Hoboken, N.J. : John Wiley & Sons, Inc., 2013)
Solid guidance for managers and trustees to better position their nonprofits now and in the future The Great Recession has left a paradigm shift for nonprofit leadership and their board members as fiduciaries. It has changed how boards make, evaluate and document investment decisions, the risks they are willing to take and the way these details are communicated to donors. Nonprofit Investment and Development Solutions + Website will provide solid guidance for nonprofit leadership, staff and volunteers to better position their nonprofits to thrive now and in the future.
The EvaluationSummary; CHAPTER 11: Socially Responsible Investing; The Roots of Socially Responsible Investing; What Exactly Is Socially Responsible Investing?; How Do We Accomplish Socially Responsible Investing?; The Risks of Socially Responsible Investing; Additional Means of Accomplishing SRI; Why Does a Nonprofit Implement an SRI Portfolio?; Summary; CHAPTER 12: The Changing Landscape for Fundraising; Our New Reality; Donor Motivations; Communication Strategies; Revenue Source Diversification; The Strategic Development Plan; Understanding Donors; Effective Communication Tools
Includes index.
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Nonprofit organizations -- United States -- Finance -- Management; Investments -- United States; Associations sans but lucratif -- x; Investissements; BUSINESS & ECONOMICS -- Personal Finance -- Investing; Investments; Nonprofit organizations -- Finance -- Management; United States